Habitual low carbohydrate high fat diet compared with omnivorous, vegan, and vegetarian diets - Bogataj Jontez, Nives; Kenig, Saša; Šik Novak, Karin; Petelin, Ana; Jenko Pražnikar, Zala; Mohorko, Nina (Frontiers in Nutrition, 2023)
Background: Dietary patterns which exclude whole food groups, such as vegetarian, vegan and low carbohydrate high fat diet (LCHF), are increasingly popular in general public. When carefully planned, all these diets have some known benefits for health, but concerns are also raised in particular for LCHF. The quality of LCHF diet which individuals follow in real life without supervision is not known. Methods: 130 healthy individuals with stable body mass following LCHF, vegan, vegetarian and omnivorous diet for at least six months, were compared in a cross-sectional study. Diet was analyzed through 3-day food records and FFQ, anthropometric measurements were performed and serum metabolic biomarkers determined form fasting blood. The study was registered at ClinicalTrials.gov under the number NCT04347213. Results: Participants on LCHF diet had the intakes of micronutrients comparable to other groups, while the intakes of macronutrients differed in line with the definition of each diet. The intakes of saturated fats, cholesterol and animal proteins were significantly higher and the intakes of sugars and dietary fibers were lower compared to other groups. Healthy eating index 2015 in this group was the lowest. There were no differences in the levels of glucose, triacylglycerols and CRP among groups. Total and LDL cholesterol levels were significantly higher in LCHF group, in particular in participants with higher ketogenic ratio. Fatty acids intakes and intakes of cholesterol, dietary fibers and animal proteins explained 40 % of variance in total cholesterol level, with saturated fatty acids being the strongest positive predictor and monounsaturated fatty acids a negative predictor. Conclusion: None of the self-advised diets provided all the necessary nutrients in optimal levels. Due to the detected increased levels of serum cholesterols, selection of healthy fat sources, higher intake of dietary fibers and partial replacing of animal sources with plant sources of foods should be recommended to the individuals selecting LCFH dietary pattern.